First Case of Gynandromorphism in the Orchid-Bee Eulaema meriana (Olivier) (Hymenoptera: Apidae) - Pazmiño-Palomino, Alex; de Oliveira, Marcio Luiz (Sociobiology, 2021)
The discovery of the first case of gynandromorphism in Eulaema meriana (Olivier) is described and illustrated. A specimen from Los Ríos, western Ecuador, discovered in the Instituto Nacional de Biodiversidad (MECN) collection, exhibits mostly male features on the left and female features on the right, except for the jugal comb of the hind wing and terminalia. This finding is compared to other reported cases in orchid bees.